Human Rights and Reformist Islam - Kadivar, Mohsen (In Translation: Modern Muslim Thinkers Ser., 2020)
Argues for the compatibility human rights and Islam, focusing on six controversial case studies: religious discrimination; gender discrimination; slavery; freedom of religion; punishment of apostasy; and arbitrary or harsh punishments.